Chemoproteomic target deconvolution reveals Histone Deacetylases as targets of (R)-lipoic acid - Lechner, Severin; Steimbach, Raphael R.; Wang, Longlong; Deline, Marshall L.; Chang, Yun-Chien; Fromme, Tobias; Klingenspor, Martin; Matthias, Patrick; Miller, Aubry K.; Médard, Guillaume; Kuster, Bernhard (Nature Communications, 2023)
Lipoic acid is an essential enzyme cofactor in central metabolic pathways. Due to its claimed antioxidant properties, racemic (R/S)-lipoic acid is used as a food supplement but is also investigated as a pharmaceutical in over 180 clinical trials covering a broad range of diseases. Moreover, (R/S)-lipoic acid is an approved drug for the treatment of diabetic neuropathy. However, its mechanism of action remains elusive. Here, we performed chemoproteomics-aided target deconvolution of lipoic acid and its active close analog lipoamide. We find that histone deacetylases HDAC1, HDAC2, HDAC3, HDAC6, HDAC8, and HDAC10 are molecular targets of the reduced form of lipoic acid and lipoamide. Importantly, only the naturally occurring (R)-enantiomer inhibits HDACs at physiologically relevant concentrations and leads to hyperacetylation of HDAC substrates. The inhibition of HDACs by (R)-lipoic acid and lipoamide explain why both compounds prevent stress granule formation in cells and may also provide a molecular rationale for many other phenotypic effects elicited by lipoic acid.
Gesehen am 31.10.2023